Gender Differences in Patients' Beliefs About Biological, Environmental, Behavioral, and Psychological Risk Factors in a Cardiac Rehabilitation Program - Mozhgan Saeidi; Saeid Komasi; Ali Soroush; Ali Zakiei; Jalal Shakeri (Journal of Cardio-Thoracic Medicine, 2014)
Introduction: There are significant gender differences in the epidemiology and presentation of cardiovascular diseases (CVDs), physiological aspects of CVDs, response to diagnostic tests or interventions, and prevalence or incidence of the associated risk factors. Considering the independent influence of gender on early dire consequences of such diseases, this study was conducted to investigate gender differences in patients' beliefs about biological, environmental, behavioral, and psychological risk factors in a cardiac rehabilitation program. Materials and Methods: This study has cross sectional design. The sample was composed of 775 patients referred to cardiac rehabilitation unit in Imam Ali Hospital in Kermanshah, Iran. The data were collected using clinical interview and patients’ medical records. The data were analyzed using descriptive statistics such as mean, standard deviation, and chi-square test​​. To do the statistical analysis, SPSS version 20 was utilized. Results: As the results indicated, there was a significant difference between the beliefs of men and women about risk factors of heart disease (X2= 48.36; P